Pengaruh Tingkat Pendidikan, Kemiskinan, Dan Pertumbuhan Ekonomi, Terhadap Indeks Pembangunan Manusia (IPM) Di Indonesia Tahun 2012-2022: Studi Kasus Provinsi Sumatera Selatan - Fathu Rohma; Fikri Muh Latif Al Haqqi; Khusnul Khotimah; Muhammad Kurniawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Human development is a development process with the aim of being able to have more choices, through a Human Development Index it can be used as a benchmark, especially in income, health and education. The aim of this research is to find out how the Human Development Index (HDI) has developed in South Sumatra in 2012-2022 and to analyze how big the influence of education, poverty and economic growth has been on the Human Development Index (HDI) in case studies in the province of South Sumatra. The table shows that the development of HDI has increased with the medium or medium HDI category during the 2018-2022 period until it was able to achieve the HDI target set by the government. Economic growth has a positive and significant effect on HDI, while education and poverty have a significant negative effect on HDI. The conclusion is that HDI development has increased during 2012-2022, poverty and education have a negative effect, while economic growth has a positive effect on the Human Development Index. Through this research, it is recommended that in government planning policies not only look at achieving the target of increasing economic growth but also the target of increasing human development because economic growth alone is not sufficient to improve the quality of human resources, especially in the aspects of education, health and people's income.